Kepemimpinan Visioner Kiai dalam Mengimplementasikan Visi di Pondok Pesantren - Zuhri Zuhri (Bidayatuna, 2018)
Educational process services are integration of educational processes and outcomes standards. Educational institutions apply service standards based on the future design of the institution as an organization, namely the Vision. Educational institutions have a vision and organizational goals as guides in achieving their goals, so are Islamic boarding schools.